2017
DOI: 10.1111/nmo.13051
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of fecal incontinence in obese patients: A prospective case‐matched study of 201 patients

Abstract: Obese patients with FI had a comparable severity of FI to that of non-obese patients with FI. Regarding obesity in patients with FI, physicians should focus on stool consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
3
21
0
2
Order By: Relevance
“…Similar to women with FI, the rectal threshold volume for discomfort was correlated with BMI in healthy women; the BET was also correlated with BMI in this study. However, the BMI was not associated with these parameters in men, either due to a type II error or because among men, the distribution of BMI values was tighter.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to women with FI, the rectal threshold volume for discomfort was correlated with BMI in healthy women; the BET was also correlated with BMI in this study. However, the BMI was not associated with these parameters in men, either due to a type II error or because among men, the distribution of BMI values was tighter.…”
Section: Discussionsupporting
confidence: 70%
“…Whether this represents an inability to simulate defecation in an artificial environment or asymptomatic pelvic floor dysfunction is unclear. While increased BMI and bariatric surgery are risk factors for FI, the effect of increased BMI on rectoanal pressures in asymptomatic healthy people is unknown. Hence, the objectives of this study were to define normal values for rectoanal pressures measured with HRM in men and women, to evaluate the relationship between rectoanal pressures with age and BMI in asymptomatic people, and to compare rectoanal pressures in asymptomatic people with a normal and prolonged BET.…”
Section: Introductionmentioning
confidence: 99%
“…In neurological patients, the objective is to obtain normal or hard stools because soft or liquid stools are not easily retained in the presence of neurological sphincter deficiency. Normalization of stool consistency is also needed to correct FI in many other etiologies . Finally, patients with SB are sometimes compared to those with anorectal malformation because both are congenital disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of stool consistency is also needed to correct FI in many other etiologies. 13,21 Finally, patients with SB are sometimes compared to those with anorectal malformation because both are congenital disorders. A study 22 evaluating the management of digestive disorders in patients with anorectal malformation showed that large enemas improved constipation but could worsen incontinence because the stool was too liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of constipation was performed using the validated Knowles–Eccersley–Scott [constipation] Symptom (KESS) score . Quality of life was quantified using a validated scale for gastrointestinal complaints (Gastrointestinal Quality of Life Index, GIQLI) as previously published in studies of faecal incontinence cohorts .…”
Section: Methodsmentioning
confidence: 99%